Exploring The Factors Affecting Consumer Preparedness For Smart Home Technology In Indonesia - Novita, Endah; Prasetio, Adhi (Publisher Cv. Inara, 2024)
SSmart home technology is becoming more popular globally, including in Indonesia. However, its adoption is still early, mainly due to the public's limited awareness of this technology. This study uses the Technology Readiness and Acceptance Model (TRAM) to assess individuals' readiness to embrace smart home technology. This research was conducted using SEM PLS with 271 respondents selected through purposive sampling, using 34 questions with a 5-point Likert scale. Positive outlook and user-friendliness have a role in how people value smart home technology, according to the study's findings. Optimism, inventiveness, and discomfort all affecthow easy something is to use. Anxiety and unease can play a role in how we interpret danger. Smart home technology adoption is influenced by factors such as its perceived value, simplicity of use, and cost significantly and positively.